Efeitos da suplementação dietética de farinha integral de abelha Apis mellifera na redução de esteatose hepática em camundongos obesos - Aline Lopes Nascimento (2022)
The diseases related to metabolism have increased worldwide, becoming epidemic, and the metabolic syndrome, which is defined as a group of risk factors that directly contribute to the development of cardiovascular disease, type 2 diabetes and liver disease. Among liver diseases, hepatic steatosis is associated with nutritional deficiency. With the difficulty in acquiring foods with high nutritional and functional value, the consumption of insects has shown satisfactory results regarding the high nutritional value and health benefits. The Apis mellifera bee is a source of nutritional and functional food when related to health benefits. Within this context, the present study evaluated the effects of the inclusion of Apis mellifera bee meal on the metabolism of obese mice induced by a hyperlipidic diet. For this, male mice of the swiss strain, after an induction to obesity, were fed for 4 weeks and distributed in 6 groups, being them: Standard Diet (AIN93G); Standard Diet (AIN93G + 15% Apis mellifera meal); Standard Diet (AIN93G + 30% Apis mellifera meal); High Fat Diet (HFD); High Fat Diet (HFD+ 15% Apis mellifera meal); High Fat Diet (HFD + 30% Apis mellifera meal). Liver weight, anthropometric data, liver tissue histology and mRNA expression were evaluated as parameters. The main results of inclusion of Apis mellifera flour induced reduction of hepatic steatosis, weight, reduction of adiposity and specific changes in histological parameters. In addition, there were also significant changes in gene expression, since, Apis mellifera flour modulated the gene expression the SREBP1 gene and the PPARg gene, an important lipid modulator, also modulated positively the GPX4 gene, which exerts cellular protection against damage caused by oxidative stress, thus highlighting the beneficial effects of Apis mellifera bee flour, on the metabolic health of mice. The main findings showed the potential of Apis mellifera bee meal in reducing hepatic steatosis in the body. Therefore, it is concluded that the inclusion of Apis mellifera insect meal in the diet generates beneficial effects on metabolic health.